Transformational Leadership of School Principals in Encouraging School Innovation Programs (Case Study of SDS IT Candra Buana Cipinang, Cibatu District, Purwakarta Regency) - Asep Mulyana; Tanti Fitri Yana (Konsultan Jurnal Ilmiah Indonesia, 2025)
This study aims to analyze the principal's application of transformational leadership in driving innovation programs at SDS IT Candra Buana, an integrated Islamic elementary school located in a rural area. Transformational leadership is understood as a leadership style that emphasizes role modeling, inspiration, intellectual encouragement, and individual attention in creating change and an innovative culture in the school environment. This study uses a qualitative approach with a case study method. Data collection techniques were carried out through in-depth interviews, observation, and documentation of the principal, teachers, students, and the school committee. Data were analyzed using the steps of reduction, presentation, verification, and validity were tested through triangulation and peer discussions. The results of the study indicate that the principal has implemented transformational leadership effectively. He is able to inspire teachers, build a collaborative work culture, and empower all elements of the school. Innovations developed include digitalization of learning, character strengthening through the ODAS program, teacher training, student independent projects, and the use of social media for school publications. Supporting factors include an open leadership style, the enthusiasm of young teachers, and committee support. Meanwhile, limited facilities, funding, and human resources become obstacles that actually encourage creativity and solidarity. This research aligns with previous studies on the positive influence of transformational leadership on the development of organizational culture and educational innovation. Contextually, these findings indicate that transformational leadership is effectively implemented in integrated Islamic schools, even amidst the limitations of rural environments.